Telemedicine a need for ethical and legal guidelines in South Africa - Caron L. Jack; Maurice Mars (South African Family Practice)
Background: Telemedicine is viewed as a new way of offering medical services. It is seen as a means of overcoming the growing shortage of health practitioners is developing countries. The aim of this paper is to highlight the need for the formulation of guidelines for the ethical practice of telemedicine in South Africa.